Study on the physicochemical and emulsifying property of proteins extracted from Pleurotus tuoliensis. (November 2021) - Fan, Hong-Bo; Zou, Yuan; Huang, Si-Yun; Liu, Ying-Li; Zheng, Qian-Wang; Guo, Li-Qiong; Lin, Jun-Fang
Abstract: Food-derived Pickering emulsifiers, particularly proteins, are environmentally friendly and receive considerable attention for the edibility. In this study, Pleurotus tuoliensis protein was extracted at pH 7 ( P. tuoliensis albumin, PTA) and pH 9.5 ( P. tuoliensis protein isolate, PTPI). PTA and PTPI contained sufficient essential amino acids for humans, but low solubility. Therefore, the pH-cycle method was applied to improve the dispersity. Compared with PTA-NP (PTA nanoparticle), PTPI-NP (PTPI nanoparticle) had smaller particle size, higher surface hydrophobicity and wettability. The advantage in particle size and surface hydrophobicity not only made PTPI-NP show faster adsorption behavior at the oil-water interface at 0.1 mg/mL, but also kept the droplet size of PTPI-NP stabilized emulsions more similar at various oil contents (0.1–0.5). After 30 d storage, the creaming and oiling off behavior of PTA-NP and PTPI-NP stabilized emulsions were unchanged. These results showed that P. tuoliensis protein, especially PTPI, could be used as natural emulsifiers in food industry. Highlights: PTPI particles had higher surface hydrophobicity and wettability, but smaller size. PTPI particles stabilized the droplet size of emulsions at low oil content. PTA and PTPI particles reduced droplet size in a concentration dependent way. PTA and PTPI particles improved store stability of emulsions at low oil content.